Penerapan Model Pembelajaran Berbasis Proyek Lapbook Untuk Meningkatkan Keterampilan Sosial Warga Belajar Pada Pembelajaran PKN Kesetaraan Paket C Kelas XII di PKBM Hidayah Probolinggo - Maharani, Kristanti; Widodo, Widodo (J+PLUS UNESA, 2024)
This research aims to analyze and describe the application of the lapbook project-based learning model and analyze the supporting and inhibiting factors for the application of the lapbook project-based learning model and the social skills of students in class XII package C equivalency PKN learning. The research method used is a descriptive qualitative method with data collection techniques in the form of in-depth interviews, participant observation and documentation. The data analysis techniques used in this research are data reduction, data presentation, drawing conclusions and verification. The research results show, there are 6 stages of implementing the project-based learning model, namely 1) Providing basic questions at the start of learning, 2) Planning the project, 3) Scheduling the project activity stages, 4) Supervising the ongoing project, 5) Assessing, 6) Evaluating the project. The social skills of learning citizens are characterized by 3 things. First, being able to solve problems well, citizens learn to exchange ideas, they give each other opinions. Second, being able to interact and communicate effectively, citizens learn to be brave enough to express their opinions, dare to ask questions. Third, being able to work well together and helping fellow citizens learn to be sensitive to friends who need help, easy to talk to and to complete projects together. In its implementation there are supporting factors, namely learning media, facilities and infrastructure as well as the curriculum and social environment. Meanwhile, the inhibiting factors in the lapbook project-based learning model process for improving social skills are physical and psychological factors and interest in learning.